Neuroendocrine dysfunction and insomniain mild traumatic brain injury patients. (1st January 2016) - Zhou, Daoyang; Zhao, Yiming; Wan, Yingfeng; Wang, Yirong; Xie, Dajiang; Lu, Qin; Yang, Shuxu; Qi, Xuchen
Highlights: mTBI patients suffer from various insomnia symptoms. mTBI patients experience more serious insomnia than objective measurements. Insomnia following mTBI was associated with HPA function dysregulation. Abstract: Mild traumatic brain injury (mTBI) has been a growing public health concern in the worldwide. To investigate the subjective and objective characteristics of insomnia following mTBI and the association between insomnia and hypothalamic–pituitary–adrenal (HPA) function of mTBI patients, 59 patients with mTBI (mTBI group) were compared with 50 healthy participants (control group) in the present study. The subjective and objective measures of insomnia were respectively obtained from Pittsburgh Sleep Quality (PSQI) and polysomnography (PSG). HPA function was measured with low-dose short synacthen test (LDSST). According to the comparative and correlation analysis of the two groups, for PSQI, the scores of sleep syndrome, sleep latency, sleep efficiency, overall sleep quality and daytime dysfunction of mTBI patients were all higher, however only sleep efficiency and daytime dysfunction of mTBI patients were related with peak cortisol on lDSST; while for PSG, sleep efficiency (SE) was lower and wake after sleep onset (WASO) was longer in mTBI patients, moreover SE and WASO of mTBI patients were correlated with peak cortisol on LDSTT; for HPA function indexes, only peak cortisol on LDSST was lower in mTBI patients. These findings suggested that mTBI patients experienced more serious subjective insomnia symptoms than objective measurement, which were associated with HPA dysfunction. This study may contribute to identifying better treatment for mTBI patients with insomnia.